2012
DOI: 10.1152/ajpheart.00093.2012
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular vortex formation is unaffected by diastolic impairment

Abstract: Normal left ventricular (LV) filling occurs rapidly early in diastole caused by a progressive pressure gradient within the ventricle and with a low left atrial pressure. This normal diastolic function is altered in patients with heart failure. Such impairment of diastolic filling is manifested as an abrupt deceleration of the early filling wave velocity. Although variations within the early filling wave have been observed previously, the underlying hydrodynamic mechanisms are not well understood. Previously, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 40 publications
5
18
0
Order By: Relevance
“…In fact, the ratio VFT/EF, which removes the influence of EF on the VFT value, presents a non-significant difference between the two groups, meaning that VFT does not provide information incremental to EF in this specific clinical context. These results are similar to those recently reported by Stewart et al (Stewart et al, 2012), in which the VFT was shown not to weigh on overall cardiac function, but in fact just a sign of optimal LV filling.…”
Section: Energetic Flow Aspectssupporting
confidence: 91%
“…In fact, the ratio VFT/EF, which removes the influence of EF on the VFT value, presents a non-significant difference between the two groups, meaning that VFT does not provide information incremental to EF in this specific clinical context. These results are similar to those recently reported by Stewart et al (Stewart et al, 2012), in which the VFT was shown not to weigh on overall cardiac function, but in fact just a sign of optimal LV filling.…”
Section: Energetic Flow Aspectssupporting
confidence: 91%
“…Our quantitative analysis of the anterior and apical vortices by estimating their vorticity could help to improve the assessment of the heart function in the echocardiographic laboratory. The recent research studies have also revealed an emerging clinical interest for characterization of intra-ventricular flow velocities and supported our findings in this research study [1,2,45,46,62,63,85,86,94,132,133]. Rodevand et al…”
Section: P = 0004supporting
confidence: 90%
“…LV vortex quantification parameters, such as vorticity, could be useful in the assessment of LV and RV diastolic (dys-)function [1,8,9,11,12]. In recent studies, vorticity was shown to be a marker of diastolic dysfunction, both in the LV [9] and the RV [8] of patients with pulmonary hypertension.…”
Section: Vorticity Inside the LV During Diastolic Fillingmentioning
confidence: 99%
“…Vorticity, the curl of velocity, is a fundamental quantity in fluid mechanics that describes the local spinning rate of fluid particles and can characterize vortex flow [10]. Quantitative vortex parameters, such as vorticity, have been used to assess diastolic (dys) function in several patient groups [8,9,11,12]. Furthermore, in patients with complex congenital intracardiac deformations such as after the Fontan operation, flow collision with remaining septal structures and stagnation of flow through a ventricular septal defect may result in altered EL and vortex formation [13].…”
Section: Introductionmentioning
confidence: 99%